1988
DOI: 10.1021/j100325a006
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of a reaction of silylene with deuterium

Abstract: A laser flash photolysis/laser absorption technique has been used to generate and monitor SiH2 radicals in real time. We present preliminary results of a study of the rate of removal of SiH2 radicals in the presence of D2 in the temperature interval 268-330 K. The removal rate coefficient is found to be temperature independent in this range with a value (1.88 ± 0.17) X 10"12 cm3 molecule"1 s'1. The implications of this result for the temperature dependence of the reaction of SiH2 with H2 are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 1 publication
1
50
0
Order By: Relevance
“…Prior to this study we have found no pressure dependencies in kinetic systems [13,16,17] involving SiMez (unlike those for SiHz [18,19]). Total pressures are listed in Table I.…”
Section: Resultsmentioning
confidence: 75%
“…Prior to this study we have found no pressure dependencies in kinetic systems [13,16,17] involving SiMez (unlike those for SiHz [18,19]). Total pressures are listed in Table I.…”
Section: Resultsmentioning
confidence: 75%
“…The apparatus and equipment for these studies have been described in detail previously [24,25]. Only essential and brief details are therefore included here.…”
Section: Equipment Chemicals and Methodsmentioning
confidence: 99%
“…Both silylenes were detected via absorption in their strong à ( 1 B 1 ) r X ( 1 A 1 ) absorption bands, SiMe 2 at 457.9 nm 21,22 and SiH 2 at 579.39 nm (17259.50 cm -1 ), a strong vibration-rotation transition. [23][24][25] Gas mixtures for photolysis were made up containing a small pressure of precursor (PhSiH 3 between 2 and 15 mTorr; OMTS between 30 and 200 mTorr), varying pressures of substrate (C 3 H 6 up to 250 mTorr; i-C 4 H 8 up to 300 mTorr; C 2 H 4 up to 9.8 Torr) together with inert diluent (sulfur hexafluoride, SF 6 ) at total pressures between 1 and 100 Torr. Pressures were measured by capacitance manometers (MKS, Baratron).…”
Section: Methodsmentioning
confidence: 99%